Comprehensive behavioral analysis and quantification of brain free amino acids of C57BL/6J congenic mice carrying the 1473G allele in tryptophan hydroxylase‐2 - Hisatsugu Koshimizu; Nao Hirata; Keizo Takao; Keiko Toyama; Takashi Ichinose; Shigeki Furuya; Tsuyoshi Miyakawa (Wiley, 2019)
Abstract Aim Tryptophan hydroxylase 2 (Tph2) is a rate‐limiting enzyme for the biosynthesis of 5‐hydroxytryptamine (5‐HT, serotonin). Previous studies have reported that C1473G polymorphism of the murine Tph2 gene leads to decreased 5‐HT levels in the brain and abnormal behavioral phenotypes, such as impaired anxiety‐ and depression‐like behaviors. In this study, to confirm the effect of the C1473G polymorphism on mouse phenotypes, we conducted a comprehensive battery of behavioral tests and measured the amounts of brain free amino acids involved in the production of 5‐HT. Methods We obtained C57BL/6J congenic mice that were homozygous for the 1473G allele of Tph2 (1473G) and subjected them and their wild‐type littermates (1473C) to a battery of behavioral tests. Using reverse‐phase high‐performance liquid chromatography (HPLC), we measured the amounts of free amino acids in the 5‐HT and epinephrine synthetic/metabolic pathways in the frontal cortex, hippocampus, striatum, and midbrain. Results We failed to detect significant differences between genotypes in depression‐like behaviors, anxiety‐like behaviors, social behaviors, sensorimotor gaiting, or learning and memory, while 1473G mice exhibited a nominally significant impairment in gait analysis, which failed to reach study‐wide significance. In the HPLC analysis, there were no significant differences in the amounts of 5‐HT, dopamine, norepinephrine, and epinephrine in the frontal cortex, hippocampus, striatum, and midbrain. Conclusion Our findings do not support the idea that congenic C57BL/6J mice carrying the 1473G allele may represent an animal model of mood disorder under normal conditions without stress.